The role of stereotyping in a culturally diverse international business environment - Korez-Vide, Romana (Teorija in praksa, 2016)
In an increasingly globalising world coupled with the polarisation of economic, political, social and cultural forces, managers confront many challenges in the process of internationalising their firms. In the paper, we introduce a conceptual model of a firm's cross-border strategy framing and discuss the role played by stereotyping in this process. The model delineates the key links between the influences of a firm's external challenges, in particular cultural distance, with managers' perceptions of psychic distance, stereotyping and the possibilities to more efficiently adjust their interactions with these challenges. The paper discusses the reasons and ways that stereotypes influence managerial attitudes and forms of behaviour and the consequent decision making of managers in a multicultural business environment. It points to the importance of managers' requisite knowledge, skills, personal characteristics as well as learning patterns for increasing the efficiency of their interactions in a cross-cultural context.
Keywords: Intercultural relations; International business; Managerji; Managers; Medkulturni odnosi; Mednarodno poslovanje; poslovno okolje; Stereotipi; Stereotypes